Localisation of X linked recessive idiopathic hypoparathyroidism to a 1.5 Mb region on Xq26-q27. - Trump, D; Dixon, P; Mumm, S; Wooding, C; Davies, K; Schlessinger, D; Whyte, M; Thakker, R (1998)
X linked recessive idiopathic hypoparathyroidism (HPT) has been observed in two kindreds from Missouri, USA. Affected subjects, who are males, suffer from infantile onset of epilepsy and hypocalcaemia, which appears to be the result of an isolated congenital defect of parathyroid gland development; females are not affected and are normocalcaemic. The gene causing HPT has been previously mapped to a 7 cM interval, flanked centromerically by F9 and telomerically by DXS98, in Xq26-q27, and an analysis of mitochondrial DNA has established a common ancestry for these two kindreds. In order to define further the map location of HPT and thereby facilitate its isolation, we have undertaken linkage studies using polymorphic loci whose order has been established as Xcen - DXS1001 - DXS294 - DXS102 - F9 - DXS1232 - DXS984 - CDR1 - DXS105 - DXS1205 - DXS1227 - DXS98 - DXS52 - Xqter, within this region. Our results established linkage (lod score > 3) between HPT and eight of these 12 loci and indicated that the most likely location of HPT was within a 1.5 Mb interval flanked centromerically by F9 and telomerically by DXS984. Thus, the results of this study have helped to refine the map location of HPT, and this will facilitate the identification of this putative developmental gene and its role in the embryological formation of the parathyroids.